Функционирование европейских языков в эпоху глобализации: межкультурная коммуникация - Masłowa, Walentyna (Acta Polono-Ruthenica, 2008)
The processes of globalization form and direct interaction and development of European languages in the modern world. So, globalization takes out the English language into the first place in the world: about 400 mln people, living in the USA, Great Britain, Canada, Australia and New Zealand consider it their naitive language. Besides, about 1,5 mld people use English as their second and third language. But in Europe the German language takes the first place.In modern linguistics a great interest is constantly increasing towards intercultural communication. The main tasks of which are the following: prevention of communicative failures and speech conflicts in the process of intercultural contacts, transmission from one language into another, linguocultural concept, because becoming proficient in the linguo-conceptual sphere (the culture of a studying language) is the final and the most important stage in mastering a foreign language.